Pengaruh Pola Asuh Orang Tua terhadap Kepercayaan Diri Anak di Tempat Penitipan Anak Siti Hajar - Dwiva Muzdalifah Daud; Riska Riska; Putri Thalib; Nurandini Jois (Khirani: Jurnal Pendidikan Anak Usia Dini, 2025)
This study investigates the effect of different parenting styles on the development of children’s self-confidence at Siti Hajar Childcare Center, considering self-confidence as a crucial foundation for early childhood in coping with learning activities and social interactions. The research employed a combination of descriptive qualitative and quantitative approaches, using a saturated sampling technique in which all parents were included as respondents. Data were gathered through observations, interviews, documentation, and questionnaires, and subsequently analyzed using descriptive analysis and simple linear regression. The results indicate that democratic parenting has a significant positive influence on children’s self-confidence, as it encourages children to be more courageous, independent, and adaptable in social environments. Conversely, authoritarian parenting does not produce a significant positive impact, because children raised under this style tend to be anxious, hesitant, and less confident. Permissive parenting is also considered less effective, as children often show excessive confidence without adequate discipline or self-control. Therefore, the application of democratic parenting by parents at Siti Hajar Childcare Center is identified as the most influential factor in fostering and strengthening children’s self-confidence.